2019
DOI: 10.15405/epsbs.2019.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Aprocess Model Of Innovative Pedagogical Design Of University E-Learning Environment

Abstract: An increase in the number of University students has led to the possibility of the dilution of educational quality. The potential of qualitative improvement of a wide range of University courses through the use of software shows promise. Specifically, the design and testing of e-learning programs is worthy of considerable examination. In this article, a process model of an innovative pedagogical design of an elearning environment in Adonis CE software is discussed. A sequence of stages of the process model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…At this stage ICT competency was accentuated and the formation of information culture with Electronic Didactic Tools (EDT) was crucial (Almazova et al, 2018). The goal was specified in the following tasks: to form the ability to creatively solve complex practical situations by designing an academic e-learning environment (Golovko et al, 2019); the ability to build effective communication in English with different communicants.…”
Section: Methodology Of Forming Flccmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage ICT competency was accentuated and the formation of information culture with Electronic Didactic Tools (EDT) was crucial (Almazova et al, 2018). The goal was specified in the following tasks: to form the ability to creatively solve complex practical situations by designing an academic e-learning environment (Golovko et al, 2019); the ability to build effective communication in English with different communicants.…”
Section: Methodology Of Forming Flccmentioning
confidence: 99%
“…The authors' experience has shown that formation of FLCC is complicated because of students' demotivation to study English, overload with specialized subjects, decrease in time allocation to study a foreign language at a university setting, low quality of educational resources. (Golovko et al, 2019). Therefore, the implementation of the suggested model would assist in forming FLCC at an advanced level.…”
Section: Research Questionsmentioning
confidence: 99%